New Ways of Learning: Teacher Training in the Use of ICTs - Hernández, Ronald M. (2018)
Information and communication technologies (ICTs) have become a decisive resource in the field of education, and at the same time, an indispensable variable in the academic practice where we seek to use each one of the resources offered by Web 2.0. The objective of this article is to perform a critical analysis and review of the conceptual aspects of teacher training, the use of the ICTs and their implications in teacher’s daily work, as well as in the teaching-learning process. Finally, it is concluded to highlight the importance of the creation of pedagogical dimensions that indicate the training competencies a teacher must have given the new technological tendency.